Implementasi Pelayanan Administrasi Terpadu Kecamatan (Paten) di Kecamatan Genuk Kota Semarang - Afsani, Muhamad Gharyn Bintang; Ana Silviana (UNES Law Review, 2024)
Sub-district Integrated Administrative Services (PATEN) is the organization of public services in the sub-district from the application stage to the document issuance stage in one place, one of the sub-districts in Semarang City that implements the PATEN policy is Genuk Sub-district. The purpose of this study is to find out the implementation of PATEN and identify obstacles and efforts in the implementation of PATEN in Genuk Sub-district. The research method used is empirical juridical with the research specification used is descriptive analytical. The results show that the implementation of PATEN policy in Genuk Sub-district is in accordance with Article 5 of the Minister of Home Affairs Regulation Number 4 of 2010 concerning PATEN Guidelines regarding the requirements for organizing PATEN, namely substance, administration, and technical requirements. In addition, the implementation of PATEN policy in Genuk Sub-district is in accordance with the principles of PATEN implementation stated in Semarang Mayor Regulation Number 43 of 2012 on PATENT Standards in Semarang City, which includes simplicity, clarity and certainty, accuracy, security and convenience, and is supported by factors that influence the success of policy implementation which include: communication, resources, disposition and bureaucratic structure. The obstacles in the implementation of PATEN policy in Genuk Sub-district are internal constraints, namely the lack of human resources, namely employees/staff in the field of public services, while external constraints are the lack of public awareness in seeking information about filing, and the difficulty of road access to Genuk Sub-district due to frequent flooding. Efforts made to overcome obstacles are the existence of internship programs, socialization, and pumping floods with water pumps.